Community Participation in the Implementation of State Administration to Improve the Quality of Public Services Through Social Media Optimization (International Forum of Researchers and Lecturers, 2025)
Community participation is very important in the implementation of state administration and public services. The government has the responsibility to meet the needs of community services in a quality manner. However, it needs to involve community participation starting from planning, implementation, to evaluation. Social media is currently an important channel for community interaction. Therefore, it needs to be optimized as a means of community participation. This research aims to analyze the role of optimizing social media in supporting community participation in order to improve the quality of public services. This qualitative research with literature studies shows that social media can be used to receive public input, provide service information , and increase public participation. In this way, it is hoped that the government can improve the quality of public services based on input provided by the public via social media. Optimizing the use of social media needs to be done to encourage active community participation.